Perfil e recrutamento do secretariado municipal de São Carlos nas gestões PFL/DEM - PT (1997/2004) - Fonseca, Marcelo Buffa da (2012)
The public position filled by appointment directly affects the governability and governance in the Brazilian political system, either for maintenance of a stable parliamentary basis or for the formulation and implementation of effective public policies. In the current democratic scenario, the appointment of policy makers with political responsibility and technical capability becomes a key element to the success of the government and enlarges its chance of electoral success. This work argues that the appointment criteria which were used by political parties have clear influence in the increase or decrease of the respective success electoral rates; from this perspective, the electoral result of the parties in the state of São Paulo in the post-redemocratization is here shown. Lastly, in a local case study, the appointment criteria which were used by mayors from parties whose programming and ideological fields are distinct will be shown.